The accuracy of different mismatch negativity amplitude representations in predicting the levels of consciousness in patients with disorders of consciousness - Zhang, Kang; Li, Kexin; Zhang, Chunyun; Li, Xiaodong; Han, Shuai; Lv, Chuanxiang; Xie, Jingwei; Xia, Xiaoyu; Bie, Li; Guo, Yongkun (Frontiers in Neuroscience, 2023)
The mismatch negativity (MMN) index has been used to evaluate consciousness levels in patients with disorders of consciousness (DoC). Indeed, MMN has been validated for the diagnosis of vegetative state/unresponsive wakefulness syndrome (VS/UWS) and minimally conscious state (MCS). In this study, we evaluated the accuracy of different MMN amplitude representations in predicting levels of consciousness. Task-state electroencephalography (EEG) data were obtained from 67 patients with DoC (35 VS and 32 MCS). We performed a microstate analysis of the task-